2022
DOI: 10.20473/j.djmkg.v55.i2.p88-92
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between maxillary and mandibular lengths of ethnic Bataks of chronological age 9–15 years

Abstract: Background: Maxillary and mandibular growth have an important role in determining diagnosis and treatment plans. Knowledge of the growth of the maxilla and mandible becomes very important in designing a proper treatment plan and knowing the mean maxillary and mandibular lengths from the ages of 9–15 means malocclusion can be treated at the appropriate age. Purpose: The aim of this study was to determine the relationship between 9–15-year-old males and females and the length of the maxilla and mandible. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[14][15][16] This study represents the pioneering investigation into the utilization of length of cranial base and total face height measurements on the lateral cephalogram for the purpose of sex estimation in the Indonesian population, with a particular emphasis on the specific area of Yogyakarta. The lateral cephalogram has been studied in pediatric and adolescent populations of Indonesia, 18,19 but no studies have investigated cephalogram measurements for sex estimation in the Indonesian population. A previous study revealed no significant difference in angular measurements on lateral cephalograms between boys and girls aged 8-12 years.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] This study represents the pioneering investigation into the utilization of length of cranial base and total face height measurements on the lateral cephalogram for the purpose of sex estimation in the Indonesian population, with a particular emphasis on the specific area of Yogyakarta. The lateral cephalogram has been studied in pediatric and adolescent populations of Indonesia, 18,19 but no studies have investigated cephalogram measurements for sex estimation in the Indonesian population. A previous study revealed no significant difference in angular measurements on lateral cephalograms between boys and girls aged 8-12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion itself is strongly influenced by genetic and environmental factors such as early primary tooth loss, tooth persistence, the discrepancy between jaw and tooth size, an abnormal number of teeth and eruption problems, and oral habits. 4,5 With the current state of the environment in the COVID-19 pandemic, the duration of cell phone use by children will undoubtedly increase with restrictions on activities outside the home; this causes children to be unable to attend school in person, and, as an alternative, they use cell phones to communicate with teachers and obtain subject matter. In addition, this means children are often in contact with cell phones for an extended period time.…”
Section: Introductionmentioning
confidence: 99%